2020
DOI: 10.1021/acs.iecr.0c00693
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility of a Simple Fluid in Cylindrical Confinement: Molecular Simulation and Equation of State Modeling

Abstract: Fluids confined in nanoporous materials exhibit thermodynamic properties that differ from the same fluid in bulk. Recent experiments and molecular simulations suggested that the isothermal compressibility is among these properties. The compressibility determines the elastic response of a fluid to mechanical impact, and in particular, the speed of acoustic wave propagation through it. Knowledge of the compressibility of fluids confined in nanopores is needed for understanding the elastic wave propagation in flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 92 publications
1
11
0
Order By: Relevance
“…In the last two decades, numerous works published in the literature presented several attempts to develop equations of state for confined fluids. While typically those were not employed to predict compressibility, a recent work has demonstrated that it is feasible and showed that one of these equations [75] qualitatively predicts compressibility of confined fluids [81]. Therefore, another open challenge is to adapt an existing equation of state, or develop a new one, which can provide quantitative predictions for compressibility of confined fluids.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the last two decades, numerous works published in the literature presented several attempts to develop equations of state for confined fluids. While typically those were not employed to predict compressibility, a recent work has demonstrated that it is feasible and showed that one of these equations [75] qualitatively predicts compressibility of confined fluids [81]. Therefore, another open challenge is to adapt an existing equation of state, or develop a new one, which can provide quantitative predictions for compressibility of confined fluids.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of those works have been developed for the elastic properties. Dobrzanski et al explored the possibility of an EOS for confined fluids to predict the compressibility of the fluid [81]. They used the generalized van der Waals (vdW) EOS developed by Travalloni et al [75,76] for squarewell fluid confined in a cylindrical pore:…”
Section: Local Elastic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the identification of the influencing factors and their contribution to the elasticity, current research focuses on simple model systems. In recent years several experimental and theoretical studies on the elasticity of adsorbates in nanopores were published. , Previous research revealed different factors that influence the elastic properties of adsorbates. ,, The elastic moduli of adsorbates in nanoconfinement are changed as a result of the so-called solvation pressure (or adsorption stress), , which is also the cause for the well-known effect of sorption-induced deformation. , Thus, a variation of the Laplace pressure (that contributes to the solvation pressure) during the sorption process causes a change of the adsorbate’s longitudinal modulus, β ads . ,, But also for fully saturated pores at the saturation vapor pressure p 0 , the solvation pressure results in a deviation of β ads from bulk values. ,, Indeed, simulations and DFT calculations by Gor and his group showed that there is a linear relation between the adsorbate’s elasticity and the inverse pore size. , …”
Section: Introductionmentioning
confidence: 99%